Nutrient intake, digestibility, ruminal fermentation, blood metabolites and milk production efficiency of lactating crossbred dairy cows receiving fresh cassava root and various sulfur levels - Kaisoda, Thitiporn; Srakaew, Wuttikorn; Prapaiwong, Tipwadee; Kongphetsak, Pachabordee; Poolthajit, Sukanya; Wachirapakorn, Chalong (Agriculture and Natural Resources, 2022)
Importance of work: Fresh cassava root (FCR) contains a high level of hydrogen cyanide (HCN), which is toxic when consumed by ruminants. Such adverse effects are reduced by sulfur supplementation. Objectives: To investigate the effect of sulfur addition on intake, rumen fermentation, blood metabolites, milk production and quality in lactating dairy cows. Materials & Methods: Four Holstein-Friesian crossbred cows with initial mean weight (± SD) of 455.1 ± 24.0 kg in mid lactation were randomly assigned according to a 4×4 Latin square design (21 d/period). The cows were assigned to receive a total mixed ration (TMR) and FCR at 0.75% bodyweight (BW; on a dry matter basis) and then sulfur was added at four levels of FCR: 0%, 0.5%, 1% and 2%. Results: The feed intake and digestion coefficients of dry matter, protein, neutral detergent fiber and acid detergent fiber were not significantly different (p > 0.05). The ruminal pH, and blood metabolites were not significantly different (p > 0.05). Nevertheless, the total volatile fatty acids (TVFA) linearly increased (p < 0.05), and the ammonia-nitrogen (NH3-N) decreased significantly (p < 0.05) with the increasing sulfur levels in the diets. The sulfur addition in cows fed FCR had no effect on milk yield, 4% fat-corrected milk or milk composition. Thiocyanate (SCN¯) in blood and milk linearly increased (p < 0.01) as the sulfur addition increased. Main finding: FCR at 0.75% BW was promising as a supplemental feed source for lactating cows and a sulfur addition of 2% of FCR improved intake, ruminal fermentation and digestibility.